‘Happy Is the One Who Seizes Your Infants and Dashes Them against the Rocks’—Psalm 137 and Moral Injury - Steinmetz, Israel (The Evangelical quarterly, 2025)
The imprecatory psalms represent a particular challenge to reading the Old Testament as Christian Scripture. Using Psalm 137 as an example, I propose that moral injury serves as a helpful lens for interpreting such texts. Imprecatory psalms are written in the contexts of tragedy, war, oppression, and exile. They express the moral trauma of those who endure such events and offer hope that God hears, responds to, and speaks through his people, even in such circumstances.